Pengaruh Kesadaran Wajib Pajak, Kualitas Pelayanan Pajak, Dan Efektivitas Pelayanan Samsat Keliling Terhadap Kepatuhan Wajib Pajak Kendaraan Bermotor (PKB) Di Kabupaten Bangli - Indrayani, Ni Wayan; Sujana, Edy (JIMAT (Jurnal Ilmiah Mahasiswa Akuntansi) Undiksha, 2021)
This study aims to determine the effect of taxpayer awareness variables, quality of tax services and effectiveness of mobile SAMSAT services on motor vehicle taxpayer compliance (PKB) in Bangli district. The research method used in this research is quantitative research methods with primary data obtained from questionnaire data which is measured using a Likert scale. This research was conducted on Motor Vehicle Taxpayers in Bangli Regency. The population in this study were 130,056 taxpayers registered at the SAMSAT Bangli Regency Office. The sampling method was carried out by incidental sampling and the total sample was 100 respondents. The data were then analyzed by several analyzes including descriptive statistics, data quality testing, classical assumption tests and hypothesis testing with data presentation assisted by SPSS 20.Â The results of this study indicate that the taxpayer awareness variable (X1), the quality of tax services (X2), the effectiveness of mobile SAMSAT services (X3) has a positive and significant effect on motor vehicle taxpayer compliance (Y) partially.